Tracing the Footsteps of Swing Legends : Tommy Dorsey & Jo Stafford, 1939-1941 - Anderson, Tyler (My University, 2012)
The purpose of this study was to research the itinerant touring schedule of the Tommy Dorsey Big Band from 1939-1941, the years Jo Stafford toured with the group.
Color poster with text and images.
Keywords: Swing (Music)--United States--History; Dorsey, Tommy, 1905-1956; Stafford, Jo; Posters